2018
DOI: 10.5897/ajmr2018.8831
|View full text |Cite
|
Sign up to set email alerts
|

Good hygiene practices and microbiological contamination in commercial restaurants

Abstract: Food services and commercial restaurants have gained more space in people's lives. Thus, people are more concerned about food security and sanitary hygiene. The present study evaluated practices of manipulation and contamination of environments and the preparation of surfaces in commercial restaurants in Vitória-ES, Brazil. Data on good practices were collected through a checklist proposal based on the RDC 216/2004; air samples were collected via the simple sedimentation technique, while surfaces (countertops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For instance, the first Salmonella enterica subspecies enterica serovar Berta food poisoning outbreak in Italy was explained by poor hygienic practices in the kitchen and food preparation areas [ 8 ]. The hygiene status in the restaurants and in food handling services was evaluated by enumeration of the typical contamination and hygiene indicator, namely, Enterobacteriaceae, in some studies [ 11 13 ]. In fact, Enterobacteriaceae count of 4 log CFU/g or higher in foods such as sashimi was considered as unsatisfactory level [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the first Salmonella enterica subspecies enterica serovar Berta food poisoning outbreak in Italy was explained by poor hygienic practices in the kitchen and food preparation areas [ 8 ]. The hygiene status in the restaurants and in food handling services was evaluated by enumeration of the typical contamination and hygiene indicator, namely, Enterobacteriaceae, in some studies [ 11 13 ]. In fact, Enterobacteriaceae count of 4 log CFU/g or higher in foods such as sashimi was considered as unsatisfactory level [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Niger regulation defines hygiene as: "the measures and conditions necessary to control the hazards and to guarantee the properties of a foodstuff for human consumption taking into account the intended use" (Nascimento et al, 2018). Regulations and food chain controls are intended to ensure the hygiene and safety of food from farm to table.…”
Section: Hygiene In Food Preparationmentioning
confidence: 99%
“…The diagnosis of the physician confirmed that the illness is from the food poisoning or eggs allergen and further laboratory analysis led him to administer the right drugs. Five days later, the symptoms of the boy and his sisters resolved and it remains unknown if the particular family is allergic to eggs or if was just a food poisoning isolated case (Aendo et al, 2018;Nascimento et al, 2018).…”
Section: Eggs-productsmentioning
confidence: 99%
See 2 more Smart Citations